Mobilizing in a hybrid political system: the Artvin case in Turkey. Issue 4 (18th May 2020) - Ozen, Hayriye; Dogu, Burak
ABSTRACT: Hybrid political systems, which are neither rigorously liberal nor authoritarian, create ambiguous political environments for protests and social movements. We argue in this study that the power-resistance dynamics become more sophisticated within the ambiguous context of hybrid systems, such as the one in Turkey, where democratic channels are not totally suspended, but significantly weakened. Examining an episode of contention between an anti-mining movement and the Justice and Development Party (Adalet ve Kalkınma Partisi, AKP) government on the issue of gold mining in Artvin, a city in the Northeastern Black Sea region, we demonstrate that in the electoral authoritarian context of Turkey the anti-mining movement gained a political role and significance well beyond its original specific aims, transforming into a conflict between those discontented with the authoritarian features of the existing system and the incumbents of that very system. Our study implies that social movements in hybrid political systems may turn into broader struggles not only because they open up political avenues for various groups to express their resentment with the prevailing undemocratic system, but also because the hegemonic forces attempt to consolidate the existing regime by mobilizing a popular support for the repression of these mobilizations.